Lipid‐dependent coupling of secretory cargo sorting and trafficking at the trans‐Golgi network. Issue 17 (30th July 2019) - von Blume, Julia; Hausser, Angelika
Abstract : In eukaryotic cells, the trans‐Golgi network (TGN) serves as a platform for secretory cargo sorting and trafficking. In recent years, it has become evident that a complex network of lipid–lipid and lipid–protein interactions contributes to these key functions. This review addresses the role of lipids at the TGN with a particular emphasis on sphingolipids and diacylglycerol. We further highlight how these lipids couple secretory cargo sorting and trafficking for spatiotemporal coordination of protein transport to the plasma membrane. Abstract :